Study of Surface Drainage of the University Campus - Rincón, Maribet; Rincón, Benedicto (Rev. Téc. Fac. Ing. Univ. Zulia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–>The study consists on the evaluation of the University Campus drainage system by the application of a model for maxima hydrological events, that determined the design flows for return periods of 25 and 50 years. Once defined the runoff, the existent natural and artificial drainages were evaluated, turning out to be inefficient for the transport of these flows; therefore, hydraulic structures were designed for new sections corresponding to the hydraulic design. The structural calculations for the system of collectors, bridges, sewers and channels were carried out with the purpose of determining their dimensions, using a maintenance approach, in order to drain efficiently the study area